Fatigue Resistance of 01420 S Alloy Welded Joints Made by Various Welding Methods - Ovchinnikov Victor (EDP Sciences, 2021)
Fatigue characteristics of welded joints of alloy 01420C made by resistance spot welding and automatic argon arc welding are obtained. The highest durability was shown by welded joints with a longitudinal weld. Joints Produced by resistance welding and simulating the edge line of a reinforced element have a durability comparable to an unloaded weld spot, which in turn is inferior to the durability of a joint with a longitudinal weld. The durability of elements of limited cross-section with repair welding of a mechanical cut is similar to the durability of a standard sample in the form of a strip with a hole.